Redesign Visual Identity Kemasan Produk UMKM Loafjkt Menggunakan Metode Design Thinking - Ryas, Ananda Fitriah Desya; Lestari, Nur Fitri; Romadon, Yogi (Sagita Academia Journal, 2025)
Packaging has an important role in branding, not only as a protector of products, but it is also considered an effective marketing tool to represent the positive image of a brand. The purpose of this study is to redesign a visual identity on the packaging of loafjkt products, so it is expected to be able to reflect characteristics of the product by enhancing its visual identity. The methods used in this design are a design thinking with phases: define, refine, and fourth, ideate (research, design idea, and prototype), and test (application and  finals of design). This design produces a packaging design with a mascot visual as a new face of the packaging to be implemented to Loafjkt. Branding results in a whole form of communication and emotional bonding between product and consumer, which can be remembered more as Jakarta's by-product through a new visual identity.